MEDIA REALIA DALAM MENGENALKAN KOSAKATA ANAK KELOMPOK A DI TK KEMBANG TERATAI KELURAHAN LEKOBALO KECAMATAN KOTA BARAT KOTA GORONTALO - Pupung PuspaArdini; Nurhayati Ibrahim; Mohamad Zubaidi; Hijrah Syahputra (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
This study The purpose of this study was to describe the use of realia media conducted by teachers in learning. The method used in this research is descriptive qualitative. Data collection techniques used in the form of observation, interviews and documentation. Based on the results of the study, the application of Realia Media in introducing the Group A Children's Vocabulary in TK Kembang Teratai Kelurahan Lekobalo, Kecamatan Kota Barat, Kota Gorontalo, illustrates that the teacher has applied realia media in the learning process. It can be seen from the teacher preparing the real media of chickens and cats to be used as learning material and Such real media can increase vocabulary in children but there is still one child who is not fluent in speaking, there is still a long pause when children tell stories, and the child's voice when speaking is still slow. for that as a teacher must work even harder in equipping children with words related to a particular field and introducing vocabulary needs to be done continuously and must go through in various ways.